2017
DOI: 10.1007/s00404-017-4381-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type and volume of fluid hydration on labor duration of nulliparous women: a randomized controlled trial

Abstract: ClinicalTrials.gov, http://www.clinicaltrials.gov , NCT01242293.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…As a result of the screening process, n = 25 articles were excluded by assessing the full texts (n = 36), and finally 11 RCTs met the inclusion criteria in this meta-analysis (Figure 1). 5,[12][13][14][15][16][17][18][19][20][21]…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…As a result of the screening process, n = 25 articles were excluded by assessing the full texts (n = 36), and finally 11 RCTs met the inclusion criteria in this meta-analysis (Figure 1). 5,[12][13][14][15][16][17][18][19][20][21]…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Variation existed between ruptured membrane status, with two of the three studies including participants with or without ruptured membranes. 20,22 Duffy et al conducted a randomized controlled trial comparing the rate of isotonic fluid administration in nulliparous women undergoing induction of labor (n = 180) in the USA. 21 They compared 125 mL/h with 250 mL/h isotonic fluid in a cohort of 180 healthy women.…”
Section: Re Sultsmentioning
confidence: 99%
“…The study by Garmi et al (n = 300) was conducted in Israel, and aimed to also examine the effect of a change in IVT fluid rate on the duration of labor. 20 Routine care (125 mL/h Ringer's lactate) was compared with two other regimens: 250 mL/h Ringer's lactate and 125 mL/h saline with 5% glucose. 20 Both studies found no significant improvements in duration of labor when women were provided with a higher rate of IVT, within populations of nulliparous women undergoing induction of labor.…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations